STUDY OF CONVEXITY IN SETS AND FUZZY SETS (FUDMA JOURNAL OF SCIENCES, 2022)
In this paper, we present an overview of both classical and fuzzy convexity, particularly, in conjunction with continuity5 and some topological concepts, and provide proofs of some of their algebraic properties along with suitable illustrations. We have extended the work of (Ammar E. E., 1999) by proving that if  and   are two convex fuzzy sets, then , , , and  are also convex fuzzy sets. We have also shown that the convexity of a fuzzy set implies semistrict quasi-convexity
Keywords: Blackeye cowpea mosaic virus, Cowpea mottle virus, cowpea seeds, Germination; Longevity